The Interplay Between Quality of Work Life, Work Stress, and Performance Outcomes among Gen Z Employees - Pamujo, Bagas Bambang; Rusli, Lathiefa; Halimatus Saadah, Aqidah; Nurajuddin, Akhmad Novandi (International Journal of Islamic Business and Management Review, 2025)
Purpose – The objective of this paper is to analyze the influence of Quality of Work Life (QWL) on employee performance by examining the mediating role of work stress among Generation Z employees in Solo. The objective of this study is twofold: first, to elucidate the inconsistent findings in prior studies regarding the impact of QWL on performance, and second, to identify the mechanisms through which work stress shapes this relationship. Methodology/approach – The study utilizes a quantitative research design, employing data collected from 120 Generation Z employees in Solo through the administration of structured questionnaires. The data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) approach to assess both direct and indirect effects between variables. Findings –The findings reveal that QWL significantly influences employee performance both directly and indirectly. Work stress acts as a mediating factor, with higher QWL reducing stress levels, while excessive stress negatively impacts performance. These results highlight the importance of a supportive work environment in maintaining productivity and well-being. Novelty/value – This study offers empirical evidence of work stress as a mediator between QWL and performance among Generation Z employees, providing insights for organizations to enhance work-life quality, reduce stress, and boost performance in the digital workplace.